42.9k views
3 votes
!!!URGENT!!!

10 POINTS!!!

Use elimination to solve the equation.

9x+2y=-17
-11x+2y=3

User Bushes
by
5.3k points

1 Answer

2 votes

Answer:

/ Solve equation [2] for the variable y


[2] 7y = 12x + 17


[2] y = 12x/7 + 17/7

// Plug this in for variable y in equation [1]


[1] 9x - 2•(12x/7+17/7) = -3

[1] 39x/7 = 13/7

[1] 39x = 13

// Solve equation [1] for the variable x



[1] 39x = 13


[1] x = 1/3

// By now we know this much :


x = 1/3

y = 12x/7+17/7

// Use the x value to solve for y


y = (12/7)(1/3)+17/7 = 3

Solution :

{x,y} = {1/3,3}



Explanation:


User Sphereinabox
by
5.5k points